(3GdCOhjI GdeaQOIs - (3CejI Hf YHO GdYRjR GdCfOdSj, CHh GdUdJ,J (B529 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH ChQOJ ajg LedI ef GdCOhjI GdeaQOI , eQJHI HMSH CaYGdgG ai LejY GdHOf hai YVh ef CYVGFg s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA GdcdGe Ydi eQHi GdLRQ (B: (3jRjO ai GdHGg hjSNf GdeYOI GdHGQOI hGdcdi hUaJg (B: (3jDNP ef GdLRQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B65 - (3U(B165s
(3GfXQ agQS GdWH HQbe (B4 (3GdCOhjI GdeaQOI (B"s
(3GfXQg eY (B" (3JMUjd ZQV GdbGUO Qbe(B" 44" 362 "s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B9 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs